2022
DOI: 10.33158/asb.r153.v8.2022
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management in soybean crop for high yields using organomineral fertilizers

Abstract: The objective of this work was to evaluate the performance of soybean cultivars as a function of the application of organomineral fertilizer via foliar, to obtain high yields. The study was conducted at the municipality of Mineiros-GO, Brazil. The soil is classified as neosol quartzeneic ortic typical, with medium texture. The experimental design was a 5x3 factorial, totaling 15 treatments, corresponding to five doses of Potamol Plus® (0, 0.25, 0.5, 0.75 and 1 L ha-1) and 3 cultivars of (M7739, M8372 and TMG70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bagateli et al (2022) reported that the application of N to wheat did not change the physiological quality of the seeds, but it promoted an 11% increase in grain yield. Ferreira et al (2022) observed that the application of foliar nitrogen fertilizers did not influence the yield performance of soybean. For the number of nodes per plant, the different management of N resulted in a positive effect with an increase in the number of nodes compared to the treatment without N in coverage, except for the total application of N in R2 (120R2/0R5), which showed no difference.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Bagateli et al (2022) reported that the application of N to wheat did not change the physiological quality of the seeds, but it promoted an 11% increase in grain yield. Ferreira et al (2022) observed that the application of foliar nitrogen fertilizers did not influence the yield performance of soybean. For the number of nodes per plant, the different management of N resulted in a positive effect with an increase in the number of nodes compared to the treatment without N in coverage, except for the total application of N in R2 (120R2/0R5), which showed no difference.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have evaluated the effects of nitrogen fertilization, both base and in coverage, and of biological nitrogen fixation (BNF) in the soybean culture (Hardarson et al, 1984;Barbosa et al, 2021;Chiluwal et al, 2021;Ferreira et al, 2022). For some researchers, the nitrogen demand is completely met by BNF, and no significant yield gains are observed with the use of nitrogen fertilizers, which, in some situations, are even negative to the BNF process and negatively affect grain yield, in addition to burdening production costs (Barbosa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%